Diffusion Kurtosis Imaging of Microstructural Changes in Gray Matter Nucleus in Parkinson Disease - Bingbing, Gao; Yujing, Zhou; Yanwei, Miao; Chunbo, Dong; Weiwei, Wang; Shiyun, Tian; Yangyingqiu, Liu; Jin, Shang; Qingwei, Song; Ailian, Liu; Lizhi, Xie (Frontiers in Neurology, 2020)
Objective: To exploit the microstructure damage of extrapyramidal system gray mater nuclei in Parkinson disease (PD) using diffusion kurtosis imaging (DKI). Materials and Methods: 35 clinically confirmed PD patients and 23 healthy volunteers are enrolled. All patients undergo MR examination with conventional MRI scan sequences and additional DKI sequence. We reconstruct the DKI raw images and analyze the data. A radiologist in our hospital collects the Mini-Mental State Examination (MMSE) score of all subjects. Results: In PD group, the mean kurtosis decreases in substantia nigra (SN) while increases in globus pallidus (GP); Mean diffusion increases in putamen, GP, thalamus, red nucleus (RN) and SN; Fractional anisotropy decreases in putamen while increases in GP and RN (P <0.05). The largest area under ROC curve of radial diffusion in GP is 0.830. Majority of kurtosis parameters show positive correlation with MMSE score, and several diffusivity parameters show negative correlation. Conclusion: DKI can qualitatively distinguish PD from healthy controls, furthermore, DKI derived parameters can quantitatively evaluate the modifications of microstructures in extrapyramidal system gray matter nucleus in PD.